Micelles versus Ribbons: how congeners drive the self-assembly of acidic sophorolipid biosurfactants - Dhasaiyan, Prabhu; Griel, Patrick Le; Roelants, Sophie; Redant, Emile; Bogaert, Inge N. A. Van; Prevost, Sylvain Francois; Prasad, Bhagavatula L. V.; Baccile, Niki (ChemPhysChem, 2017)
Sophorolipids (SLs), a class of microbially derived biosurfactants, are reported by different research groups to have different self-assembled structures (either micelles or giant ribbons) under the same conditions. Here we explore the reasons behind these contradictory results and attribute these differences to the role of specific congeners that are present in minute quantities. We show that a sample composed of a majority of oleic acid (C18:1) sophorolipid in the presence of only 0.5 % (or more) of congeners with stearic acid (C18:0) or linoleic acid (C18:2) results in the formation of micelles that are stable over long periods of time. Conversely, the presence of only 10 to 15 % of congeners with a stearic acid chain gives fibrillar structures instead of micelles. To study the mechanisms responsible, oleic acid SLs devoid of any other congeners were prepared. Very interestingly, this sample can self-assemble into either micelles or fibers depending on minute modifications to the self-assembly conditions. The findings are supported by light scattering, small-angle X-ray scattering, transmission electron microscopy under cryogenic conditions, high-pressure liquid chromatography, and NMR spectroscopy.

Microwave assisted batch and continuous flow synthesis of palladium supported on magnetic nickel nanocrystals and their evaluation as reusable catalyst - Nikam, Arun V.; Kulkarni, Amol A.; Prasad, Bhagavatula L. V. (Crystal Growth & Design, 2017)
Palladium nanocrystals (NCs) supported on nickel NCs (Pd/Ni) were synthesized in a continuous flow manner by the microwave-assisted method in the presence and absence of oleylamine. Parameters optimized for batch experiments were considered while performing continuous flow synthesis. The Pd/Ni NCs synthesized in the presence of oleylamine displayed good catalytic activity for hydrogenation of aromatic nitro compounds, and those bearing alkene, and alkyne moieties. The ferromagnetic character of the supporting nickel NCs allowed the recovery of the catalyst and these recovered catalysts could be reused several times.

Mechanistic aspects of methanol electro-oxidation reaction through cyclic voltammetry: is it correct to blame carbon monoxide for catalyst poisoning? - Deshpande, Pooja S.; Chaudhari, Vijay R.; Prasad, Bhagavatula L. V. (Energy Technology, 2020)
The mechanism of the methanol oxidation reaction is revisited using systematic cyclic voltammetric studies. These studies clearly indicate that the peak during the cathodic scan belongs mainly to electro-oxidation of the carbon monoxide, and that only a fraction of this carbon monoxide remains adsorbed on the electrode, contrary to what previous reports suggested. More details can be found in article number by Bhagavatula L. V. Prasad and co-workers.
Keywords: carbon monoxide; cyclic voltammetry; electrocatalysts; electrode poisoning; Methanol oxidation